Aqueous extracts of Vaccinium corymbosum as inhibitors of Staphylococcus aureus - Silva, Sara; Costa, Eduardo M.; Costa, Mª Rosário; Pereira, Miguel F.; Pereira, Joana O.; Soares, José C.; Pintado, Mª Manuela (Food control, 2015)
Staphylococcus aureus has been established has one of the most common pathogens causing nosocomial infections worldwide and also playing a role in for several outbreaks related to the consumption of contaminated foodstuffs. More recently, the discovery of methicillin resistant S. aureus (MRSA) in raw and processed foods increased the risk factor associated with S. aureus associated foodborne diseases and has led to the search for new sources of antimicrobial agents. Therefore the aim of this study is to evaluate, for the first time, the impact of Vaccinium corymbosum L., fruit and leaf, infusions and decoctions upon methicillin resistant (MRSA) and sensitive S. aureus (MSSA). In order to accomplish these objectives V. corymbosum extracts were characterized and inhibition halos, inhibitory concentrations, impact upon enzymatic activity and biofilm formation were assessed. The results obtained showed that major compounds present in V. corymbosum constitution were quercetin-3-glucoside, chlorogenic and cafeic acids. MRSA and MSSA growth was inhibited at 12.5 mg/mL, for leaf, and 50 mg/mL, for fruit, and sub-MIC concentrations presented inhibition percentages as high as 3 log of viable cells and 47% of biomass. Furthermore DNase and coagulase were also inhibited at sub-MIC concentrations of the extracts. The results obtained imply an effective antibacterial and antibiofilm activity of these extracts towards MRSA and MSSA, thus revealing an interest potential for application in the food industry either as a functional ingredient or a preservative. •Fruit and leaf extracts are rich in phenolic compounds.•All extracts inhibit both MRSA and MSSA.•All extracts exhibit antibiofilm activity.•Enzymatic activity was affected by the presence of the extracts.